(untitled) (Indian Journal of Animal Production and Management, 2014)
Due to consumer appeal for higher fat deposit and preference of tougher meat and yellowish colour carcass by the Mizo people, broilers are reared up to 3- 4 months of age till they weigh around 4 - 5 kg. The study was conducted to compare the performance of broiler under Intensive and Backyard System of management, for which 300 commercial broilers were reared in three replicates (100 birds in one replicate) under Intensive System in the College farm and another 300 birds were reared at farmers level under Backyard System in 10 replicates (30 birds / farmers). All the birds were reared up to 6th weeks of age and thirty birds from each rearing system were randomly selected (10 birds per replicate from Intensive System and 3 birds per replicate from Backyard System) and slaughtered to study some important carcass characters. Remaining birds under both the rearing systems were reared up to 3 months of age and another similarly selected 60 birds (30 birds per rearing group) were utilized for carcass study. The live weights of broilers at 6th week and at 13th week were significantly (P<0.05) higher in intensive system; however dressing percentage was found to be significant only at 6th week. Non-significant differences (P<0.05) were observed in carcass quality parameters like pH, Water Holding Capacity, Extract Release Volume between the carcasses of birds under two rearing system both at 6th and 13th weeks of age. However, significant difference (p > 0.05) was observed in shank, liver and giblet weight and in total meat and bone yield both at 6th weeks and at 13th weeks of age.